The Regulatory Framework for Volunteering in the Russian Federation - Elena V. Skripchenkova, Natalia I. Gorlova, Zulfiya A. Troska,; Rezeda R. Khairutdinova, Larisa I. Starovojtova, (Opción, 2019)
The aim of the study is to investigate the regulatory framework for volunteering in the Russian Federation via comparative qualitative research methods. As a result, State Programs and orders, public budget loans and subsidies shall be provided on competitive basis, the performer shall be selected without any privileges but from the perspective of efficiency assessment. The conclusion is made about the necessity to adopt a specialized federal law on volunteering.